Myocardial Ischemia and Reperfusion Leads to Transient CD8 Immune Deficiency and Accelerated Immunosenescence in CMV-Seropositive Patients. Issue 1 (2nd January 2015) - Hoffmann, Jedrzej; Shmeleva, Evgeniya V.; Boag, Stephen E.; Fiser, Karel; Bagnall, Alan; Murali, Santosh; Dimmick, Ian; Pircher, Hanspeter; Martin-Ruiz, Carmen; Egred, Mohaned; Keavney, Bernard; von Zglinicki, Thomas; et al.
Abstract : Rationale: : There is mounting evidence of a higher incidence of coronary heart disease in cytomegalovirus-seropositive individuals. Objective: : The aim of this study was to investigate whether acute myocardial infarction triggers an inflammatory T-cell response that might lead to accelerated immunosenescence in cytomegalovirus-seropositive patients. Methods and Results: : Thirty-four patients with acute myocardial infarction undergoing primary percutaneous coronary intervention were longitudinally studied within 3 months after reperfusion (Cohort A). In addition, 54 patients with acute myocardial infarction and chronic myocardial infarction were analyzed in a cross-sectional study (Cohort B). Cytomegalovirus-seropositive patients demonstrated a greater fall in the concentration of terminally differentiated CD8 effector memory T cells (TEMRA ) in peripheral blood during the first 30 minutes of reperfusion compared with cytomegalovirus-seronegative patients (−192 versus −63 cells/μL; P =0.008), correlating with the expression of programmed cell death-1 before primary percutaneous coronary intervention ( r =0.8; P =0.0002). A significant proportion of TEMRA cells remained depleted for ≥3 months in cytomegalovirus-seropositive patients. Using high-throughput 13-parameter flow cytometry and human leukocyte antigen class I cytomegalovirus-specific dextramers, we confirmed an acute and persistent depletion of terminally differentiated TEMRA and cytomegalovirus-specific CD8 + cells in cytomegalovirus-seropositive patients. Long-term reconstitution of the TEMRA pool in chronic cytomegalovirus-seropositive postmyocardial infarction patients was associated with signs of terminal differentiation including an increase in killer cell lectin-like receptor subfamily G member 1 and shorter telomere length in CD8 + T cells (2225 versus 3397 bp; P <0.001). Conclusions: : Myocardial ischemia and reperfusion in cytomegalovirus-seropositive patients undergoing primary percutaneous coronary intervention leads to acute loss of antigen-specific, terminally differentiated CD8 T cells, possibly through programmed cell death-1–dependent programmed cell death. Our results suggest that acute myocardial infarction and reperfusion accelerate immunosenescence in cytomegalovirus-seropositive patients. Abstract : Supplemental Digital Content is available in the text.